An 18 Years Old Male with Leptospirosis: A Case Report - Heri Pribadhi; Ni Made Dewi Arimas; Made Dinda Pratiwi (Universitas Pendidikan Ganesha, 2026)
Leptospirosis is a zoonotic bacterial infection caused by pathogenic Leptospira species and remains a major public health concern in tropical and subtropical regions. Early clinical manifestations are often nonspecific and resemble other acute febrile illnesses, leading to delayed diagnosis and treatment. Severe leptospirosis may develop even in young and previously healthy individuals, resulting in significant morbidity and mortality. An 18-year-old male presented with acute-onset fever, severe arthralgia, nausea, and vomiting. He had a history of environmental exposure, including frequent flooding around his residence and the presence of rodents. Physical examination revealed fever, conjunctival injection, and jaundice. Laboratory findings showed thrombocytopenia, acute kidney injury, and marked hyperbilirubinemia with mildly elevated transaminases. Serological testing for Leptospira IgM was positive, confirming the diagnosis. Abdominal ultrasonography demonstrated no biliary obstruction or structural liver abnormalities. The patient was treated with intravenous ceftriaxone, adequate fluid resuscitation, and close monitoring of renal function. Clinical and laboratory improvements were observed, and the patient was discharged in stable condition after six days of hospitalization. This case highlights that severe leptospirosis can occur in adolescents and young adults without comorbidities. Recognition of environmental risk factors, early diagnosis, and prompt initiation of appropriate antimicrobial and supportive therapy are crucial to prevent severe complications. Increased clinical awareness is essential to improve outcomes in leptospirosis-endemic areas.